Life-Cycle Assessment of High-Strength Concrete Mixtures with Copper Slag as Sand Replacement. (2nd January 2019) - Gursel, Aysegul Petek; Ostertag, Claudia
Abstract : Aggregate consumption rates have now exceeded natural renewal rates, signaling shortages both locally and globally. Even more concerning is that the worldwide markets for construction aggregates are projected to grow at an annual rate of 5.2% in the near future. This increase is attributed to rapid population growth coupled with the economic development worldwide. In terms of material availability, one of the most vulnerable regions is the Asia-Pacific region specifically, Singapore, where there is higher demand but limited availability of natural sand and gravel for use as aggregates in concrete construction projects. This paper focuses mainly on the environmental impacts of fine aggregate alternatives used in high-strength concrete applications in Singapore, which is one of the major global importers of natural sand following China. Singapore has been experiencing political and environmental challenges linked to the shortage of natural sand use as aggregates, even while the demand is increasing in the construction sector. Copper slag, a readily available waste material from shipyards in Singapore, is a possible replacement material for a portion of the natural sand in concrete mixtures, thus sustaining the projected growth in the region. A life-cycle assessment approach is applied to investigate the environmental impacts of copper slag and its alternative use as natural sand in high-strength concrete applications in Singapore. The system boundary consists of the major production processes of concrete constituents (including Portland cement and fine and coarse aggregates, with CS considered as fine aggregate) from a cradle-to-gate perspective, consisting of relevant life-cycle phases of raw materials extraction, transportation, and production processes at the relevant facility where the production occurs. Output from the assessment is provided in terms of embodied energy use and air emissions of concrete mixes with varying percentages of copper slag as fine aggregate. Results show that environmental impacts of aggregates decrease with the increasing substitution rate of natural sand with copper slag when calculated on the basis per unit volume of the concrete mix. For example, 40% and 100% sand replacements with copper slag result in a reduction of 8% and 40% in embodied energy, 12% and 30% in global warming potential, 8% and 41% in acidification, and 7% and 35% in particulate matter formation, respectively. Normalized impacts (i.e., normalized with respect to compressive strength) are observed to remain at almost similar levels for concrete mixes with up to 40% natural sand having been replaced with copper slag. Therefore, it is recommended that replacement of fine aggregates by 40–50% of copper slag (by weight) will produce concrete mixtures with comparable environmental impacts while maintaining feasible durability and strength properties.